Mutagenic characterization of a conserved functional amino acid in fuculose-1-phosphate aldolase from Methanococcus jannaschii, a hyperthermophic archaea - Yoon, HS; Kwon, S; Han, MS; Yu, Yeon-Gyu; Yoon, MY (KOREAN SOC APPLIED MICROBIOLOGY, 2001)
To elucidate the putative role of the amido group in the metal binding of the fuculose-1-phosphate aldolase from Methanococcus jannaschii, we have examined a potential target using site-directed mutagenesis. The replacement of asparagine 25 with leucine or threonine was shown to have a negative effect, not only on catalytic efficiency, but also on substrate recognition as well. The Hill coefficient values yielded a value of approximate to1. All metals used with the wild-type aldolases exhibited higher activity than that of the mutants. The spectra of the mutants were quite different from the wildtype aldolase. A highly conserved amino acid of asparagine 25 in a related family of aldolase does not appear to provide sufficient evidence for evolution.
Keywords: AQUIFEX PYROPHILUS; ESCHERICHIA-COLI; CLASS-II; OVERPRODUCTION; PURIFICATION; THERMOPHILE; SPECIFICITY; MECHANISM; ENZYMES